Developing a Quality of Cancer Survivorship Care Framework: Implications for Clinical Care, Research, and Policy - Nekhlyudov, Larissa; Mollica, Michelle A; Jacobsen, Paul B; Mayer, Deborah K; Shulman, Lawrence N; Geiger, Ann M (JNCI : Journal of the National Cancer Institute, 2019)
There are now close to 17 million cancer survivors in the United States, and this number is expected to continue to grow. One decade ago the Institute of Medicine report, From Cancer Patient to Cancer Survivor: Lost in Transition, outlined 10 recommendations aiming to provide coordinated, comprehensive care for cancer survivors. Although there has been noteworthy progress made since the release of the report, gaps remain in research, clinical practice, and policy. Specifically, the recommendation calling for the development of quality measures in cancer survivorship care has yet to be fulfilled. In this commentary, we describe the development of a comprehensive, evidence-based cancer survivorship care quality framework and propose the next steps to systematically apply it in clinical settings, research, and policy.